2008
DOI: 10.1111/j.1600-6143.2008.02399.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immunosuppressive Treatment on Endothelial Biomarkers After Kidney Transplantation

Abstract: Endothelial dysfunction occurs in hemodialysis and kidney-transplanted patients and can be enhanced by immunosuppressive therapy. Circulating endothelial cells (CEC), endothelial microparticles (EMP) and sVCAM-1 provide information on endothelium activation and damage.We compared the impact of two immunosuppressive regimens (CsA/Aza vs. Tac/MMF) on the kinetics of CEC, EMP and sVCAM-1 levels in 52 patients, both before graft and 3, 6, 9 and 12 months after graft, in reference to 50 healthy controls.CEC, EMP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 54 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…Long-term changes in circulating microparticles levels in patients with kidney transplantation were previously reported in a smaller patient population (15, 16). …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Long-term changes in circulating microparticles levels in patients with kidney transplantation were previously reported in a smaller patient population (15, 16). …”
Section: Discussionmentioning
confidence: 78%
“…In kidney transplant recipients, levels of circulating EMP were significantly decreased one year after transplantation, as compared to pretransplant values in the same patients. Interestingly, patients on cyclosporine and azathioprine immunosuppressive regimen had lower EMP levels post-transplant, as compared to patients who were on tacrolimus and mycophenolate immunosuppressive treatment (16). …”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments are required to determine whether the plasma values of these biomarkers may have been higher in the absence of MMF. In addition, these discrepancies could be related to the direct assessment of vascular function in our study when compared with indirect quantification of biomarkers (14). Finally, we observed that the vascular function in the transplanted aorta, which is abrogated in control rats (39), was improved by CsA and MMF and, to a greater extent, by the combination of CsA and MMF.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, CsA inhibits the enterohepatic recirculation of MMF and, thus, promotes its elimination (38). Previous data obtained in humans did not suggest these beneficial vascular effects because circulating levels of endothelial cells and vascular cell adhesion molecule-1 were found to be high in transplanted patients treated with tacrolimus, an other CNI, associated with MMF (14). Additional experiments are required to determine whether the plasma values of these biomarkers may have been higher in the absence of MMF.…”
Section: Discussionmentioning
confidence: 93%
“…They reported the beneficial impact of renal transplantation on endothelial injury through circulating levels of endothelial markers and concluded that these effects are more pronounced in patients treated by CsA/Aza and are impaired in relation with cytomegalovirus (CMV) and cardiovascular diseases. These results are suggestive of the noninvasive endothelial evaluation as an early index of vascular injury [66].…”
Section: Microparticles In Kidney Transplantationmentioning
confidence: 60%